The Great Plains during World War II - Hurt, R. Douglas (Book collections on Project MUSE., 2008)
Although the impact of World War II was not as transformative for the Great Plains as it was for other areas of the United States, it was still significant and tumultuous. Emphasizing the region?s social and economic history, The Great Plains during World War II is the first book to examine the effects of the war on the region and the responses of its residents. Beginning with the isolationist debate that preceded the war, R. Douglas Hurt traces the residents? changing view of the European conflict and its direct impact on the plains. Hurt argues that the people of the Great Plains based their.